# Re: ?? Functional Dependency Question ??

Date: Tue, 21 Oct 2008 06:53:15 -0700 (PDT)

Message-ID: <854d6c64-29e3-4bab-8143-6dc53a746214_at_g25g2000prf.googlegroups.com>

On Oct 21, 8:15 pm, paul c <toledobythe..._at_oohay.ac> wrote:

*> David BL wrote:
**>
**> ...
**>
**> > RTP: (X->A)(Y->B) -> XY->AB
**>
*

> > (X->A)(Y->B) : premise

*> > X->A, Y->B : conjunction elimination
**> > XY : premise
**> > X,Y : conjunction elimination
**> > A : modus ponens on X,X->A
**> > B : modus ponens on Y,Y->B
**> > AB : conjunction introduction
**> > XY->AB : conditional proof
**> > (X->A)(Y->B) -> XY->AB : conditional proof
**>
**> I can see that the second step is eliminating a "conjunction" but the
**> fourth step doesn't seem to me to involve a conjunction.
*

Step 3: Premise XY (the conjunction of X and Y). Step 4: From XY deduce X and deduce Y (known as conjunction elimination). Received on Tue Oct 21 2008 - 15:53:15 CEST